TEACHER-ADAPTED MATERIALS IN TEACHING ENGLISH AT A SECONDARY SCHOOL - Saputri, Yusyfiyah Adinda; Dollah, Syarifuddin; Muhalim, Muhalim (Universitas Negeri Makassar, 2024)
This study aims to find out why teachers adapted materials in teaching English at secondary school and how teachers adapted the materials. The researcher applied a case study qualitative method. To achieve the research objectives, the data were collected by comparing documents and interviews. English teachers of MAN 2 Makassar who were using adapted materials, implementing the Merdeka Curriculum, and teaching in grades X and XI served as the study’s subject. The result of this study showed that: (1) The reasons teachers adapted the materials are the students’ condition which is more complex nowadays, the unsuitability of existing materials to students’ English proficiency, and the limitation of time allocation. (2) The first teacher applied adding, modifying, reordering, and simplifying, while the second teacher applied deleting and simplifying in adapting the existing materials.